An Analysis of Child Poverty and Social Policies in Turkey - Gurses, Didem (SAGE PUBLICATIONS INDIA PVT LTD, 2009)
Recent economic and social developments together with the impacts of globalization have caused an increase in the incidence of poverty in Turkey. This article, after providing a general overview of the poverty profile aims to analyze child poverty. The situation of the children is examined in relation to health, education and child labour. The existing social protection mechanisms are presented and evaluated in relation to their impacts on child well-being. The article concludes with a summary of the findings and policy implications on the issue.
Keywords: Turkey; poverty; childhood poverty; protection mechanisms; inequality; social policy; Development Studies